Climatic factor of soil wind erosion in the Steppe of Ukraine: spatial analysis - Chornyy, S. G. (AgroChemistry and Soil Science, 2024)
Wind erosion in the Steppe of Ukraine, which depends on a number of natural and anthropogenic factors, is largely determined by specific climatic conditions. These conditions, in addition to wind strength and constancy, include air temperature, precipitation, and evaporation. These parameters collectively determine the water balance of the soil. Wet surfaces are stable enough to resist strong winds, while a dry soil layer with low moisture is enough to initiate wind erosion. To achieve the goal of the study – spatial analysis of wind erosion hazard – the climate factor (C) from the Wind Erosion Equation (WEQ) mathematical model used to estimate the average long-term soil loss by wind. For this purpose, we used standard data on wind speed, temperature, and precipitation from meteorological stations in the Ukrainian Steppe, as well as published generalizations of long-term average wind speed, monthly precipitation, and temperature. To estimate the climatic parameter for wind erosion, we used meteorological observation data from 33 stations in the Steppe of Ukraine, as well as from adjacent territories in Moldova and the Russian Federation. The calculations and mapping of the climate factor from the WEQ model showed that its values depend on the spatial distribution of all its components – the average wind speed and the Thorntheit "effective precipitation" index. In the northern Steppe of Ukraine, where the value of the effective precipitation index is highest and wind speed remains stable between 3 to 5 m/s, the climatic factor for wind erosion is minimal – less than 10. In the coastal regions of Odesa, Mykolaiv, and Kherson oblasts, as well as in the steppe Crimea, where the effective precipitation index is minimal (30 – 45) and the average long-term wind speed exceeds 6 m/s, the C index ranges from 25 to 35. Considering the anti-deflation resistance of the soil, the areas with sod-sandy soils, clay-sandy soils, and soil-like sandy substrates in the lower reaches of the Dnipro River (Oleshky Sands) are the most wind erosion-prone areas in the entire Ukrainian Steppe. These areas have the lowest resistance to strong winds and, despite their relatively high value of the climatic factor of wind erosion (C), are the most vulnerable to wind erosion.